1977
DOI: 10.1007/bf01457846
|View full text |Cite
|
Sign up to set email alerts
|

Viloxazine, sleep, and subjective feelings

Abstract: The sleep of eight volunteers (mean age 55) was recorded electrophysiologically while viloxazine 200 mg was taken daily for 3 weeks, preceded and followed by a week of matching blanks. The volunteers also made ratings of their feelings on visual analogue scales. Another 15 volunteers (mean age 34) took viloxazine 300 mg daily for 3 weeks, preceded and followed by 3 weeks of matching blanks, and they also made daily ratings of feelings. The drug diminished sleep duration and caused more frequent and longer tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The effects upon REM sleep produced by desipramine, a TCA with predominantly NE reuptake inhibition, confirm earlier clinical observations reported for this agent (Shipley et al 1985;Kupfer et al 1991) as well as other selective NE reuptake inhibitors such as viloxazine, maprotiline, Org 4428, and reboxetine (Brezinova et al 1977;Nicholson and Pascoe 1986;Van Bemmel et al 1999;Farina et al 2002). The results demonstrate that sole NE reuptake inhibition, achieved by a pharmacological intervention, has an effect on sleep polygraphic variables similar to that of most antidepressant medications, i.e.…”
Section: Effect On Sleep Architecturesupporting
confidence: 86%
See 1 more Smart Citation
“…The effects upon REM sleep produced by desipramine, a TCA with predominantly NE reuptake inhibition, confirm earlier clinical observations reported for this agent (Shipley et al 1985;Kupfer et al 1991) as well as other selective NE reuptake inhibitors such as viloxazine, maprotiline, Org 4428, and reboxetine (Brezinova et al 1977;Nicholson and Pascoe 1986;Van Bemmel et al 1999;Farina et al 2002). The results demonstrate that sole NE reuptake inhibition, achieved by a pharmacological intervention, has an effect on sleep polygraphic variables similar to that of most antidepressant medications, i.e.…”
Section: Effect On Sleep Architecturesupporting
confidence: 86%
“…Interestingly, literature reports of increases in stage 2 sleep have also appeared for specific NE reuptake inhibitors such as maprotiline Pascoe 1986) andOrg 4428 (Van Bemmel et al 1999) as well as SNRIs such as venlafaxine (Salin-Pascual et al 1997) and clomipramine (Steiger 1988). Duloxetine 60 mg BID, but not 80 mg QD or desipramine, also significantly decreased SWS duration, an effect previously reported with viloxazine (Brezinova et al 1977), clomipramine (Steiger 1988), and fluoxetine (Gillin et al 1997).…”
Section: Effect On Sleep Architecturementioning
confidence: 64%
“…Although there were trends to lesser wakefulness, these were not consistently significant and sleep was not made longer. Among the objective measures, it was found that trazodone reduced REM sleep, as is true of other antidepressant drugs, such as tricyclics Gillin et al, 1978), the monoamine oxidase inhibitors (Dunleavy & Oswald, 1973), viloxazine (Brezinova et al, 1977) or mianserin (Morgan et al, 1980). What was unusual was trazodone's effect in increasing SWS, which has rarely been reported as an effect of any drug though, among drugs used for mood disorders, it has been found for lithium (Chernick & Mendels, 1973;Kupfer et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Vogel (1983), REM sleep deprivation was, and still is, thought to be the mechanism of action of antidepressant drugs, although this REM sleep suppressive effect does not occur with iprindole (Baxter and Gluckman 1969) or viloxazine (Brezinova 1977). According to our data, trazodone should be added to these peculiar drugs whose effects suggest that the REM sleep suppressant effect of most antidepressant products might well represent the consequence, and not the mechanism of their antidepressant effects (Mouret 1982).…”
Section: Electroencephalographymentioning
confidence: 99%